An engagement framework for the authentic co-design of a consent and healthy relationships intervention with upper-secondary students - Pantaleo, Ashleigh M.; Dzidic, Peta L.; Newnham, Elizabeth; Chih, HuiJun; Wells, Robert; Olson, Brad; Langley, Sarah; Schonfeld, Adrian; Hendriks, Jacqueline (Frontiers in Reproductive Health, 2024)
IntroductionThe objective of this demand driven research is to co-design an intervention for upper-secondary students that addresses issues of consent and healthy relationships. In this paper, we (university researchers, student co-researchers, school staff), present the engagement framework that has been critical to the project's development and planned implementation.MethodsAn iterative co-design approach grounded in a participatory research approach is currently being adopted. Student co-researchers from three independent secondary schools on Whadjuk Nyungar Country in Boorloo/Perth, Western Australia, have been engaged as co-researchers in the design of the intervention. Supplementary quantitative and qualitative data from students enrolled at each school site is also being collated to further inform the intervention design. Student co-researchers will provide insights on the overarching design of the intervention including: the scope of key concepts they want to learn, interpretation of supplementary data, and the development of contextually relevant educative content.ResultsRetrospective and prospective components of the engagement framework are described and supported with applied examples where applicable. Preliminary results demonstrate the imperative of adopting iterative co-design, and the efficacy of our authentic engagement framework. A draft intervention has been formalized and will soon undergo piloting. The co-design process has already resulted in an intervention that differs from the initial program first conceptualized by university researchers.ConclusionImperative to our engagement framework is centering students as experts of their lived experience. It is anticipated that this engagement framework will provide insights around the feasibility, value, and necessity for authentic engagement of upper-secondary school students in the design of their consent and healthy relationship education.